Blood transfusion - Britten,Anthony F.H. (New Delhi World Health Organization, 1994)
A practical common-sense guide to the efficient organization and management of blood transfusion services. Developed during a series of workshops held in the Eastern Mediterranean region, the manual aims to help new services profit from global experience while encouraging established services to upgrade their practices and policies in line with rapid advances in blood banking technology. Information responds to the distinct needs and conditions seen in Eastern Mediterranean countries. Adopting a problem-oriented approach, the manual concentrates on three areas responsible for most weaknesses and most errors in the region's blood transfusion services: organization and management, blood donor motivation and blood collection, and quality assurance. Case studies and examples of country experiences are used throughout the text to facilitate understanding of day-to-day procedures as well as fundamental principles. The core of the manual consists of three detailed chapters covering the organization and management of blood transfusion services, the recruitment of donors and blood collection, and the complete range of management and operational systems needed for quality assurance.
Keywords: Blood transfusion